Sarcoid in cancer patients: clinical characteristics and associated disease status - Kiess, Ana; Wang, Hangjun; Travis, William; Yahalom, Joachim (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background:  The increased risk of cancer in patients with sarcoidosis is well established, but there is little information regarding sarcoid diagnosed during or following cancer.  The purpose of this study is to describe and analyze the disease status and events associated with the diagnosis of sarcoid in cancer patients.Methods:  At a large cancer center, we identified 64 patients with a pathologic diagnosis of sarcoid-like granuloma during or following a diagnosis of malignancy.  Pathology specimens were re-examined by experts, and clinical and imaging information were reviewed.  Disease-related events including recurrence, progression, death, and second malignancy were analyzed. Results:  The most common primary malignancies were breast (17%), lymphoma (16%), lung (13%), and testicular cancer (11%). Thirty-six out of 64 patients (56%) were diagnosed with sarcoid within 10 months of their primary malignancy, whereas 28 (44%) were diagnosed with sarcoid in follow-up, including 15/28 without evidence of disease, 6 with associated diagnosis of recurrence, 5 with associated diagnosis of second malignancy, 1 with stable disease, and 1 with progressive disease.  Sarcoid biopsy sites included mediastinal nodes (59%), hilar nodes (13%), lung (30%), and other nodes (17%), and the reason for biopsy was usually abnormal imaging (66%).  Sarcoid and tumor were co-localized in 34%.  Including long-term follow-up events, sarcoid was present in association with 10 of 19 recurrences (53%) and 8 of 12 second malignancies (67%).Conclusion:  While sarcoid often presents at initial diagnosis or staging of cancer, in a significant number of patients, it appears in association with recurrence or second malignancy.